Leo Strauss on Plato's Euthyphro : the 1948 notebook, with lectures and critical writings - Strauss, Leo (The Pennsylvania State University Press, 2023)
"An examination of Leo Strauss's 1948 notebook and other writings on the Euthyphro, Plato's dialogue on piety, using close analysis and line-by-line commentary"--